Reactive Photo-Fenton ceramic membranes: Synthesis, characterization and antifouling performance. (1st November 2018) - Sun, Shaobin; Yao, Hong; Fu, Wanyi; Hua, Likun; Zhang, Guangshan; Zhang, Wen
Abstract: To develop reactive and antifouling membrane filtration systems, a photo-Fenton ceramic membrane was prepared by coating goethite (α-FeOOH) catalysts on a zirconia/titania alumina membrane via a cross-linking method. Scanning electron microscopy (SEM), X-ray diffraction spectroscopy (XRD) and Fourier transform infrared spectroscopy (FTIR) were used to characterize α-FeOOH catalysts and the surface coating quality. The cross linker yielded stable covalent binding between catalyst and membrane under room temperature and produced a homogeneous and smooth coating of catalyst on ceramic membranes. Photo-Fenton reactions were initiated with addition of H2 O2 under UV irradiation to improve the foulant degradation on membrane surface while filtration. Membrane fouling was simulated by bovine serum albumin (BSA) and humic acid (HA). Our results show that the photo-Fenton reactions on the coated membranes slowed down the fouling kinetics and even reversed the fouling, leading to a stable transmembrane pressure (TMP) over time of filtration, as opposed to a monotonous increase of TMP due to surface fouling. The batch experiments verified that the photo-Fenton reactions achieved the degradation rates of 76% and 86% for HA and BSA respectively within 60 min, with the mineralization rates of over 80% as indicated by the total organic carbon measurement. This study embarks on a novel antifouling membrane filtration process via incorporation of photo-Fenton reactions. The findings are also important for diverse applications of surface fouling mitigation and rationale design of fouling resistant surfaces or materials through photo-Fenton or other catalytic reactions. Graphical abstract: Image 1 Highlights: Photo-Fenton catalysts are coated on ceramic membranes via cross-linking under room temperature. Photo-Fenton reaction mitigates membrane fouling caused by BSA and humic acid. The catalytic activity of the functionalized ceramic membrane is stable after chemical cleaning.